2023
DOI: 10.3389/fmed.2023.1140787
|View full text |Cite
|
Sign up to set email alerts
|

Associations between intimate partner violence and adverse birth outcomes during pregnancy: a systematic review and meta-analysis

Cancan Guo,
Mengtong Wan,
Yue Wang
et al.

Abstract: BackgroundIntimate partner violence (IPV) has been associated with an elevated risk of multiple adverse birth outcomes, yet little is known about how specific IPV influences adverse birth outcomes. The aim of this study was to examine the association between IPV during pregnancy and adverse birth outcomes (i.e., preterm birth, low birth weight, and stillbirth).MethodsSystematic searches were conducted using four databases: EMBASE, Web of Science, PubMed, and CINAHL for observational studies published from 1 Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Domestic violence during pregnancy can have significant adverse impacts on both the woman and her newborn child [ 51 ]. Studies have shown it can lead to psychological issues for the woman, as well as disruptions in birth outcomes like low birth weight and preterm delivery [ 52 , 53 ]. Notably, emotional form of domestic violence during pregnancy appear to increase the woman’s risk of developing conditions like post-traumatic stress disorder and depression [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Domestic violence during pregnancy can have significant adverse impacts on both the woman and her newborn child [ 51 ]. Studies have shown it can lead to psychological issues for the woman, as well as disruptions in birth outcomes like low birth weight and preterm delivery [ 52 , 53 ]. Notably, emotional form of domestic violence during pregnancy appear to increase the woman’s risk of developing conditions like post-traumatic stress disorder and depression [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Domestic violence during pregnancy (DVDP) and related types of violence have been associated with multiple adverse health outcomes such as hypertension [ 31 ] and labor and delivery complications [ 32 ]. DVDP has been linked to low birth weight [ 32 – 34 ], induced and spontaneous abortion [ 35 ], miscarriages [ 3 , 6 , 12 , 36 ], stillbirth [ 37 , 38 ], under-5 mortality [ 39 , 40 ], and preterm labor [ 34 , 41 ]. DVDP has also been linked to poor utilization of healthcare services such as delayed entry into antenatal care/immunization, decreased rest, and decreased food intake [ 42 ].…”
Section: Introductionmentioning
confidence: 99%